Application of Clean and Healthy Living Behavior (PHBS) From The Household Knowledge and Attitude Study - Putri, Ronasari Mahaji; Rosdiana, Yanti; Nisa, Aprilia Choirun (Journal Of Nursing Practice, 2019)
Background: The behavior of clean and healthy life (PHBS) is an obligation to be carried out by everyone. PHBS is an effort to maintain the health of themselves and their families. The PHBS coaching program has been running for approximately 18 years, but its success is far from expected. It is necessary to explore the factors underlying the failure to implement PHBS. Mothers as educators in the family, have an obligation not only to implement PHBS for themselves, but also educate their children to conduct clean and healthy lifestyle.Purpose: The purpose of this study was to determine the application of clean and healthy behavior (PHBS) from the study of knowledge and attitudes of housewives in the household setting.Method: This research is a descriptive study with a cross sectional approach, involving 39 housewives in RT 03 RW 06 Tlogomas Malang. The sample is taken in total side. The independent variable is the knowledge and attitudes of housewives, while the dependent variable is clean and healthy living behavior. Instrument to explore knowledge, attitudes and behavior using a questionnaire. Data analysis using the Spearman rank test.Result: The results showed that as many as 43.6% of housewives were well informed, 76.9% of housewives had good attitudes, and as many as 69.2% of mothers had good PHBS. Statistical tests show there is no relationship between knowledge with PHBS (p value 0.792), and there is a relationship between attitudes and PHBS of housewives (p-value 0.007).Conclusion: The application of clean and healthy lifestyle is not related to knowledge, but is related to the attitude of housewives in RT 03 RW 06 Tlogomas Malang.